2021
DOI: 10.1002/jsfa.11342
|View full text |Cite
|
Sign up to set email alerts
|

Water mimosa (Neptunia oleracea Lour.) can fix and transfer nitrogen to rice in their intercropping system

Abstract: BACKGROUND: Cereal-legume intercropping systems are an environmentally friendly practice in sustainable agriculture. However, research on the interspecific interaction of nitrogen (N) between rice and aquatic legumes has rarely been undertaken. To address this issue, a pot experiment was conducted to investigate N utilization and the N interaction between rice and water mimosa (Neptunia oleracea Lour.) in an intercropping system. The root barrier patterns consisted of solid barrier (SB), mesh barrier (MB), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Previous studies also found that intercropping resulted in reduced growth attributes owing to inter‐species and intra‐species competition for growth resources compared with monoculture 34‐36 . However, in rice/water mimosa inter‐cropping or mix‐cropping system, rice was a stronger competitor and water mimosa was a weaker competitor 25 . Thus, rice growth better in these two cropping systems in our study.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Previous studies also found that intercropping resulted in reduced growth attributes owing to inter‐species and intra‐species competition for growth resources compared with monoculture 34‐36 . However, in rice/water mimosa inter‐cropping or mix‐cropping system, rice was a stronger competitor and water mimosa was a weaker competitor 25 . Thus, rice growth better in these two cropping systems in our study.…”
Section: Discussionsupporting
confidence: 53%
“…[34][35][36] However, in rice/water mimosa inter-cropping or mix-cropping system, rice was a stronger competitor and water mimosa was a weaker competitor. 25 Thus, rice growth better in these two cropping systems in our study.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations